Permainan Tradisional Congklak terhadap Pengembangan Kecerdasan Logis Matematis Anak - Rahmadayanti, Rahmadayanti; Sehan, Iis (Journal of Telenursing (JOTING), 2024)
This research aims to determine the influence of traditional games on the development of children's mathematical logical intelligence in preschool Kartika and Dta Al-Bilal, Karawang district in 2023. The method used is a quasi-experimental type with a non-equivalent control group design approach. The research results show that the Wilcoxon test results show the asymp value. Sig. (2-taileid) is <.001 < 0.005, so it can be concluded that ho is rejected and ha is accepted, thus it can be concluded that there is an influence of the traditional game congklak on the development of children's mathematical logical intelligence in the Kartika preschool, Karawang district in 2023. The conclusion of this research is that there is an influence of traditional games on the development of children's mathematical logical intelligence at Paud Kartika and Dta Al-Bilal. Keywords: Children's Mathematical Logical Intelligence, Traditional Congklak Games, Development.